ANALISIS PERANCANGAN BUSINESS MODEL CANVAS (BMC) DI UD. KALI MENGAJI KECAMATAN CILONGOK KABUPATEN BANYUMAS - Yusuf Enril Fathurrohman (Agritech: Jurnal Fakultas Pertanian Universitas Muhammadiyah Purwokerto, 2022)
Palm sugar is one commodity that has the potential to be developed. UD. Kali Mengaji is one of the B2B business units that produce palm sugar. The purpose of this research is to analyze the Business Model Canvas design from UD. The method used is a descriptive qualitative approach that focuses on 9 elements of the Business Model Canvas (BMC). The results of this study indicate that the customer segment of UD. Kali Mengaji is a segmented market. Its value propositions include performance, brand, price, cost reduction, risk reduction, accessibility, and convenience/usability. The channels used are direct and indirect. Customer relationship by applying for personal assistance. The revenue stream are product sales, oven services, and warehouse rental services. Key resources include human resources, facilities, finance, and technology. Key activities are with suppliers of raw materials and production activities. Key partnerships are carried out with fostered farmers, craftsmen, collectors, and partner companies. The cost structure includes general and labor costs.